The Relationship Between Parental Education Level and Role with Bossy Behavior in Preschool Children - Suherliana; Sari, Apriani Susmita; Rosidi, Ahyar (Bantayang Omni Cendekia, 2024)
Background: Pre-school children feel superior, become pretentious, and like to rule (bossy). Bossy is a domineering, controlling and spoiled behavior that occurs in children. Education is the guidance or help provided by adults to the development of children so that they are capable enough to carry out their own life tasks. The role of parents is a set of behaviors of two parents in nurturing, guiding and educating children, as well as being consistent with certain stimuli in teaching children not to foster bossy behavior. Objective: The purpose of this study was to analyze the relationship of parental education level and role with bossy behavior in preschool children (3–5 Years). Methods: The design study used a quantitative analytical observational with cross sectional approach. A sample of 40 parents (mothers) was obtained using the total sampling technique. Data collection used a parental role questionnaire and bossy behavior questionnaire. Data analysis using the Spearman Rank statistical test. Results: There was no relationship between parents' education level and the bossy behavior of preschool children with p-value (0.146>0.05); meanwhile, there was a relationship between the role of parents and the bossy behavior p-value (0.000<0.05). Conclusion: This study found no significant relationship between parents' education levels and bossy behavior in preschool-aged children. However, there was a significant and strong correlation between parental roles and bossy behavior. Children raised by parents with good parenting roles were less likely to display bossy behavior. These findings emphasize the importance of active parental involvement and consistent parenting in reducing domineering behavior in early childhood.